Improving students' mathematical reasoning through the learning cycle instructional model - Putri, Devi Utami; Sirwanti; Aspikal (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
Mathematical reasoning is an essential skill that every student must possess as a tool to find problem-solving solutions effectively and efficiently, develop cognitive abilities, and foster critical and creative thinking in facing 21st-century challenges. However, students' mathematical reasoning skills remain low, particularly in solving and analyzing complex mathematical problems. This issue arises due to students' passive involvement in the learning process. This study aims to improve the mathematical reasoning skills of eighth-grade students through the implementation of the Learning Cycle instructional model. The research method used is Classroom Action Research (CAR). The results indicate that the average score of students' mathematical reasoning tests increased from 22.96 in the initial test to 47.85 in Cycle I and 80.64 in Cycle II. Additionally, the percentage of students meeting the mathematical reasoning competency criteria increased from 8% in the initial test to 19% in Cycle I and reached 75% in Cycle II. Based on the findings, it can be concluded that the implementation of the Learning Cycle instructional model is effective in enhancing students' mathematical reasoning skills in the topic of Probability in eighth grade. This model can serve as an alternative instructional strategy to increase student engagement and understanding in mathematics.